Perioperative course of COVID-19 in pediatric patients undergoing emergency surgeries - Raksha Kundal; Ranju Singh; Vishal Kant; Maitree Pandey; Yogesh Kumar Sarin (Wolters Kluwer Medknow Publications, 2022)
Objective: Adults with COVID-19 infection undergoing surgery have an increased risk of complications and mortality. However, literature mentioning the perioperative course and outcome of children with COVID-19 infection undergoing emergency surgery is still lacking. Therefore, we planned this study to observe the need for postoperative ventilation, oxygen requirements, and postoperative mortality in pediatric patients with COVID-19 infection scheduled for emergency surgery. Methods: After ethical committee approval, all the COVID-19-infected pediatric patients who underwent an emergency surgery from April 2020 to May 2021 were included. Data collected included details of COVID-19 disease, American Society of Anesthesiology (ASA) grading, comorbidities, perioperative details such as tachycardia or bradycardia, any oxygen desaturation (SpO2<90), need for postoperative oxygen therapy, postoperative ventilation, and recovery/death. Results: A total of 22 COVID-19-infected pediatric patients underwent emergency surgery in the study period. Fourteen (63.6%) were asymptomatic at the time of admission. Nineteen patients (86.4%) belonged to ASA grade IE and three (13.6%) patients belonged to ASA grade III E. Three patients (13.6%) had comorbidities. Only one patient had hypotension and tachycardia intraoperatively. The same patient needed postoperative ventilation and succumbed. Conclusion: Our study shows that pediatric surgical patients with COVID-19 infection do not exhibit an increased need for oxygen or postoperative ventilation, postoperative pulmonary complications, or high mortality unless there is associated comorbidity.